Electronic Toll Collection System in Bangladesh: Challenges and Prospects (Bangladesh Journal of Public Administration, 2020)
Electronic Toll Collection (ETC) system using radio frequency identification (RFID) is a digital technology that allows vehicles to pass through the toll plaza without stopping for toll payment. The most notable advantage of this technology is that it eliminates congestion near the toll booths. Toll operators could also be benefitted from the implementation of ETC. In this study, problems and prospects of introducing ETC in Bangladesh have been assessed with the help of the Questionnaire Survey and Key Informant Interview. A total of nine samples were surveyed. It was revealed from the study that there are both problems and prospects of introducing ETC in Bangladesh. Seventy percent of respondents know about the launching of ETC in Bangladesh. The respondents stalwartly perceive that ETC would help ease traffic jams created by long queues in the manual payment of toll. There are many challenges in introducing ETC in Bangladesh. As this is a new technology, it would take time to overcome the difficulties. Efforts from all corners can move the ETC forward and make excellent use of the modern and digital technology in the payment of toll in line with the viewpoint of Digital Bangladesh. Keywords: Electronic toll collection (ETC), radio frequency identification (RFID), toll plaza, questionnaire survey, key informant interview